The status and future of direct nuclear reaction measurements for stellar burning. (25th November 2021) - Aliotta, M; Buompane, R; Couder, M; Couture, A; deBoer, R J; Formicola, A; Gialanella, L; Glorius, J; Imbriani, G; Junker, M; Langer, C; Lennarz, A; et al.
Abstract: The study of stellar burning began just over 100 years ago. Nonetheless, we do not yet have a detailed picture of the nucleosynthesis within stars and how nucleosynthesis impacts stellar structure and the remnants of stellar evolution. Achieving this understanding will require precise direct measurements of the nuclear reactions involved. This report summarizes the status of direct measurements for stellar burning, focusing on developments of the last couple of decades, and offering a prospectus of near-future developments.